Pioniers of Microsurgery: the Touch of History - Špokevičius, Saulius (Lietuvos chirurgija, 2024)
Every hand and microsurgeon worldwide is more or less familiar with the names of those who are mentioned in this article: Harry Buncke, Harold E. Kleinert, Robert Acland, Hanno Millesi and Algimantas Otonas Narakas. Who ever new or were familliar with them experienced feeling as it was “the royal touch” for those who had a scropulosis in the middle ages: the touch was healing and left the unforgettable memories – they were toutched by a queen or a king. Every contact with the giants of microsurgery left noteworthy memories of their lavish lessons and cordial advises. The author had a very close professional contacts with all of them and is eager to share some of the highlights spent with them in operating rooms, writing articles and discussing subjects during the scietific meatings.